Effect of a construction educational protocol on nurses’ knowledge, performance and its effect on patient satisfaction undergoing cardiac catheterization - Eaid Elgazzar, Samia; Ismail Keshk, Lamiaa (International Journal of Advanced Nursing Studies, 2018)
Cardiac Catheterization is a life-threatening health problem, which needs standardized intervention policies, as well as it requires health provider to be skillful and high qualify to attain highest effect of management. This study aimed to investigate the effect of a construction educational protocol on nurses' knowledge, performance and its effect on patient satisfaction undergoing cardiac catheterization.Methods: This quasi-experimental study was conducting in catheterization, intensive care and cardiac care unit at general Port Said hospital in Port Said city â€“ Egypt including all nurses were worked at those units (51) and all patients admitted to cardiac catheterization unit within 6 month. Data was collected through Socio -Demographic data sheet, structured questionnaire to assess knowledge, observational checklist to assess nurses' performance and tools to assess patient sociodemographic data and patient satisfaction.Results: There was increase nurses knowledge and performance in the post educational protocol in all domains of care regarding cardiac catheterization. While, majority of patients were satisfied for the nursing care before, during and post cardiac catheterization procedure that rendered by nurses that have educational protocol. Also, strong positive correlation between nursesâ€™ knowledge and patient satisfaction at post educational protocol with statistical significant differences.Recommendation: updating knowledge and performance of nurses through implementation continuing educational protocol about cardiac catheterization; strict observation of nurses' performance when caring for cardiac catheterization patients and provision of guidance to improve of satisfaction.Â Â